MOPHOSYNTAXICS OF LANGUAGE LOCALITY MUKOMUKO DISTRICT BENGKULU PROVINCE: MORFOSINTAKSIS BAHASA LOKALITAS KABUPATEN MUKOMUKO PROVINSI BENGKULU - Rio Rinaldi; Ineng Naini; Romi Isnanda (LLDIKTI Wilayah X, 2024)
This paper aims to describe the morphosyntactic characteristics of the language of native speakers in Pauh Terenja Village, XIV Koto District, Mukomuko Regency, Bengkulu Province. This is an effort to identify language constructions based on the structure of sentences, clauses, phrases and words so as to form a unified language characteristic. Morphosyntactic studies are used as a basic basis for thinking and analysis. This type of research is qualitative with a descriptive method carried out by analyzing the syntactic level (sentences, phrases and words). Data collection was carried out through in-depth empirical observations by recording or taking notes and listening to the conversations of native speakers in interactions. Based on the research results, the local language of native speakers in Pauh Terenja Village, XIV Koto District, Mukomuko Regency, Bengkulu Province is characterized by a distinctive dialect and unique syntactic constructions that can be observed and compared with other regional languages or Indonesian. At the syntactic level, typical sentence characteristics are observed in the use of major sentences and minor sentences along with their construction characteristics. The delivery of these sentences appears in external functions (command sentences, denial sentences, news/declarative sentences, interjection sentences, interrogative sentences). In this sentence, it can be also seen the construction of phrases based on word class. Meanwhile, at the level of word form, distinctive things can be seen in the variations in morphemes, variations in allomorphs, and the function of these morphemes in sentences.